Dead‐time optimisation for a phase‐shifted dc–dc full bridge converter with GaN HEMT. Issue 9 (4th April 2016) - Joo, D.M.; Lee, B.K.; Kim, J.S.
Abstract : An accurate dead‐time adjustment method for phase‐shifted full bridge (PSFB) converter is presented. This method allows the dead‐time of converters to be optimised to meet zero voltage switching condition. The optimum dead‐time range can be predicted with high accuracy for any type of power semiconductor switch, including gallium nitride high‐electron‐mobility transistor, so that a practical design for a PSFB converter can be realised. The validity of the proposed dead‐time optimisation method was verified by experimental results with a 600 W prototype.